DEVELOPMENT OF DECISION TOOL FOR A PROBLEM-SOLVING ACTIVITY USING PAIRWISE COMPARISON TECHNIQUE TO SUPPORT AN INTUITIVE DECISION. (May 2020) - Tanaiutchawoot, N.; Bursac, N.; Gross, J.; Rapp, S.; Albers, A.
Abstract: Pairwise comparison is basically used to prioritize alternatives and select a solution in product development. Decision errors can happen when the amount of processing information increases. This research proposes an assisted decision tool to prioritize alternatives by using the pairwise comparison technique and a Quicksort algorithm. This software was evaluated in the product development workshop that aims to select the component to further develop in the new product generation. This tool provides high-reliability results, reduces procedure time and is a user-friendly interactive interface.